2014
DOI: 10.1007/s12291-014-0442-4
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Properties of Skin and Pulp Extracts of Different Grape Cultivars In Vitro and Attenuation of H2O2-Induced Oxidative Stress in Liver Tissue Ex Vivo

Abstract: Grapes are the richest source of antioxidants due to the presence of potent bioactive phytochemicals. In this study, the phytochemical contents, scavenging activities and protective role against H 2 O 2 -induced oxidative stress in liver tissue ex vivo of four grape (Vitis vinifera) cultivars extracts, namely Flame seedless (black), Kishmish chorni (black with reddish brown), Red globe (red) and Thompson seedless mutant (green), were evaluated. The total phenolics and flavonoids content in pulp or skin fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…The antioxidant capacity of the tested extracts, reflected in the delay of LPO, confirmed the ability of the biomolecules of S. chinensis to prevent and/or delay oxidative damage, which was, furthermore, validated by a good correlation with DPPH and TEAC results. Moreover, Singha and Das [ 49 ] reported that the water extract of the Omija skin and pulp exhibited a potent peroxyl radical-scavenging capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant capacity of the tested extracts, reflected in the delay of LPO, confirmed the ability of the biomolecules of S. chinensis to prevent and/or delay oxidative damage, which was, furthermore, validated by a good correlation with DPPH and TEAC results. Moreover, Singha and Das [ 49 ] reported that the water extract of the Omija skin and pulp exhibited a potent peroxyl radical-scavenging capacity.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the plant extract doses were standardised for their respective total phenolic contents as GAE analysed by the Folin-Ciocateu assay. Whilst ascorbic acid is known to interfere with this assay [ 61 ], based on analyses conducted by others [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], the contributions of ascorbic acid to the GAE results are estimated to be 0.3% and 4% for grape skin and red cabbage extracts, respectively. These minimal contributions of ascorbic acid to the GAE results reflected the naturally low ascorbic acid content of grape skin [ 62 ], and the effects of microwave cooking [ 66 ] and ultrasonication [ 67 ] which reduced the ascorbic acid content of red cabbage during plant processing.…”
Section: Discussionmentioning
confidence: 99%
“…GSH, a nonenzymatic free radical scavenger, protects tissues from oxidative stress by directly interacting with ROS or as a cofactor for enzymatic detoxification [22,23]. SOD converts superoxide radicals to H 2 O 2 that is removed by the reaction with CAT and/or GSH [24].…”
Section: Discussionmentioning
confidence: 99%